2006
DOI: 10.1016/j.micpath.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Escherichia coli IrgA homolog adhesin is regulated by the ferric uptake regulation protein

Abstract: The IrgA homologue adhesin (Iha) is an adherence-conferring outer membrane protein of Escherichia coli associated with enterohemorrhagic and uropathogenic strains. Here, we used primer extension analysis to identify iha promoters in O157:H7 and uropathogenic E. coli strains. Transcriptional fusions demonstrated that iha transcription is repressed by iron. Gel shifts using purified ferric uptake regulator protein (Fur) demonstrated that repression involves a direct interaction between Fur and the iha promoter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
(62 reference statements)
3
27
0
Order By: Relevance
“…This latter function is consistent with the fact that iha is induced under iron-limiting conditions and is subject to Fur-mediated repression in iron-replete environments in both UPEC and O157:H7 STEC strains (Leveille et al, 2006;Rashid et al, 2006b), as well as in the hyper-virulent LEE-negative STEC strain 98NK2, as shown in this study. However, the mammalian gut is a complex environment and many other compounds may impact on virulence gene expression.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This latter function is consistent with the fact that iha is induced under iron-limiting conditions and is subject to Fur-mediated repression in iron-replete environments in both UPEC and O157:H7 STEC strains (Leveille et al, 2006;Rashid et al, 2006b), as well as in the hyper-virulent LEE-negative STEC strain 98NK2, as shown in this study. However, the mammalian gut is a complex environment and many other compounds may impact on virulence gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…1b). The observation that Iha is better expressed in DMEM than LB medium has been reported previously for O157:H7 STEC, non-O157:H7 STEC and UPEC strains (Johnson et al, 2005;Rashid et al, 2006b;Schmidt et al, 2001). …”
Section: Regulation Of Iha Expression In 98nk2 By Ironsupporting
confidence: 79%
See 3 more Smart Citations